The transcription factor NF-ATc1 regulates lymphocyte proliferation and Th2 cytokine production. - Yoshida, H; Nishina, H; Takimoto, H; Marengère, L; Wakeham, A; Bouchard, D; Kong, Y; Ohteki, T; Shahinian, A; Bachmann, M; Ohashi, P; Penninger, J; et al. (1998)
NF-ATc1 is a member of a family of genes that encodes the cytoplasmic component of the nuclear factor of activated T cells (NF-AT). In activated T cells, nuclear NF-AT binds to the promoter regions of multiple cytokine genes and induces their transcription. The role of NF-ATc1 was investigated in recombination activating gene-1 (RAG-1)-deficient blastocyst complementation assays using homozygous NF-ATc1-/- mutant ES cell lines. NF-ATc1-/-/RAG-1-/- chimeric mice showed reduced numbers of thymocytes and impaired proliferation of peripheral lymphocytes, but normal production of IL-2. Induction in vitro of Th2 responses, as demonstrated by a decrease in IL-4 and IL-6 production, was impaired in mutant T cells. These data indicate that NF-ATc1 plays roles in the development of T lymphocytes and in the differentiation of the Th2 response.